2008
DOI: 10.1159/000127362
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Kidney Function in Patients with Rheumatoid Arthritis: Plasma Cystatin C versus <sup>51</sup>Cr-EDTA Clearance

Abstract: Background/Aim: Knowledge of the usefulness of cystatin C measurement in the detection of chronic kidney disease in patients with rheumatoid arthritis (RA) is scant. The purpose of this study was to evaluate the ability of plasma cystatin C- and creatinine-based methods to predict glomerular filtration rate (GFR) and classify chronic kidney disease in RA patients. Methods: The study population consisted of 64 RA patients aged 41–86 years. Comparisons were made between measured plasma creatinine, cystatin C, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
1
18
0
1
Order By: Relevance
“…Although serum cysC appears to be a more convincing marker of renal function than serum Cr in patients with RA (2,13,14), some contradictory results have also been reported (15). This study provides additional evidence to support the advantage of serum cysC measurements in patients with RA.…”
Section: Discussionmentioning
confidence: 62%
“…Although serum cysC appears to be a more convincing marker of renal function than serum Cr in patients with RA (2,13,14), some contradictory results have also been reported (15). This study provides additional evidence to support the advantage of serum cysC measurements in patients with RA.…”
Section: Discussionmentioning
confidence: 62%
“…However, most drug-dosing recommendations are based on the Cockcroft-Gault (CG) [3] formula, which estimates the creatinine clearance (CrCl). Additionally, CG remains widely used in clinical practice and recent articles and reviews continue to support its use [4,5,6,45,47,63]. …”
Section: Introductionmentioning
confidence: 99%
“…if the GFR decreases from 100 to 50 ml/min, the SCr in a small woman may increase from 0.5 to 1.0 mg/dl and, thus, still be within normal limits despite a 50% reduction in GFR). Karstila et al 10 found that the SCr was normal in 19% of rheumatoid arthritis patients with significant renal insufficiency (<60 ml/min/1.73 m 2 ) as determined by an EDTA clearance. This is consistent with our observation that 18% of patients with a normal SCr had a MDRD eGFR of <60 ml/min/ 1.73 m 2 .…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Recent studies in patients with rheumatoid arthritis and systemic lupus erythematosus have found the MDRD equations for calculating eGFR to be superior to SCr or CrCl in measuring renal function. 9,10 As a result, it has been recommended that the MDRD-based determination of eGFR be used to assess and monitor renal function in patients with lupus nephritis. 13,14 To date no studies have assessed the prognosis of severe lupus nephritis based on the baseline level of eGFR.…”
Section: Introductionmentioning
confidence: 99%